Photosynthetic inorganic carbon acquisition in an acid-tolerant, free-living species of Coccomyxa (Chlorophyta) - Verma, Vidhu; Bhatti, Shabana; Huß, Volker; Colman, Brian (Journal of Phycology, 2009)
The processes of CO acquisition were characterized for the acid-tolerant, free-living chlorophyte alga, CPCC 508. rDNA data indicate an affiliation to the genus Coccomyxa, but distinct from other known members of the genus. The alga grows over a wide range of pH from 3.0 to 9.0. External carbonic anhydrase (CA) was detected in cells grown above pH 5, with the activity increasing marginally from pH 7 to 9, but most of the CA activity was internal. The capacity for HCO uptake of cells treated with the CA inhibitor acetazolamide (AZA), was investigated by comparing the calculated rate of uncatalyzed CO formation with the rate of photosynthesis. Active bicarbonate transport occurred in cells grown in media above pH 7.0. Monitoring CO uptake and O evolution by membrane-inlet mass spectrometry demonstrated that air-grown cells reduced the CO concentration in the medium to an equilibrium concentration of 15 μM, but AZA-treated cells caused a drop in extracellular CO concentration to a compensation concentration of 27 μM at pH 8.0. CO -pulsing experiments with cells in the light indicated that the cells do not actively take up CO . An internal pool of unfixed inorganic carbon was not detected at the CO compensation concentration, probably because of the lack of active CO uptake, but was detectable at times before compensation point was reached. These results indicate that this free-living Coccomyxa possesses a CO - concentrating mechanism (CCM) due to an active bicarbonate-uptake system, unlike the Coccomyxa sp. occurring in symbiotic association with lichens. © 2009 Phycological Society of America.
Keywords: Bicarbonate transport; Carbonic anhydrase; CO2-concentrating mechanism; Dissolved inorganic carbon; Photosynthesis